Neighborhood deprivation and risk of head and neck cancer: A multilevel analysis from France. (August 2017) - Bryere, Joséphine; Menvielle, Gwenn; Dejardin, Olivier; Launay, Ludivine; Molinie, Florence; Stucker, Isabelle; Luce, Daniele; Launoy, Guy; ,
Highlights: There are no multilevel study of socioeconomic level focused on head and neck. The influence of area-level social status on head and neck cancer risk remained despite individual status. The contextual effects of deprived areas can possibly increase the risk of head and neck cancer. Abstract: Background: While it is known that cancer risk is related to area-level socioeconomic status, the extent to which these inequalities are explained by contextual effects is poorly documented especially for head and neck cancer. Methods: A case-control study, ICARE, included 2415 head and neck cancer cases and 3555 controls recruited between 2001 and 2007 from 10 French regions retrieved from a general cancer registry. Individual socioeconomic status was assessed using marital status, highest educational level and occupational social class. Area-level socioeconomic status was assessed using the French version of the European Deprivation Index (EDI). The relationship between both individual and area-based socioeconomic level and the risk of head and neck cancer was assessed by multilevel analyses. Results: A higher risk for head and neck cancer was found in divorced compared with married individuals (OR = 2.14, 95% CI = 1.78–2.57), for individuals with a basic school-leaving qualification compared with those with higher education (OR = 4.55 95% CI = 3.72–5.57), for manual workers compared with managers (OR = 4.91, 95% CI = 3.92–6.15) and for individuals living in the most deprived areas compared with those living in the most affluent ones (OR = 1.98, 95% CI = 1.64–2.41). The influence of area-level socioeconomic status measured by EDI remained after controlling for individual socioeconomic characteristics (OR = 1.51; 95% confidence interval: 1.23–1.85, p-value = 0.0003). Conclusions: The role of individual socioeconomic status in the risk of head and neck cancer is undeniable, although contextual effects of deprived areas also increase the susceptibility of individuals developing the disease.